Estrogenic activity of cylindrospermopsin and anatoxin-a and their oxidative products by FeIII-B*/H2O2. (1st April 2018) - Liu, Jishan; Hernández, Sandra E.; Swift, Simon; Singhal, Naresh
Abstract: The cyanotoxins released into waters during cyanobacterial blooms can pose serious hazards to humans and animals. Apart from their toxicological mechanisms, cyanotoxins have been shown to be involved in estrogenic activity by in vivo and in vitro assays; however, there is limited information on the change in estrogenicity of cyanotoxins following chemical oxidation. In this study, the estrogenic activity of cylindrospermopsin (CYL) and anatoxin-a (ANA) at concentrations ranging from 2.4 × 10 −7 M to 2.4 × 10 −12 M (CYL) and 7.1 × 10 −6 M to 7.1 × 10 −11 M (ANA), and after treatment by the Fe III -B*/H2 O2 catalyst system, was investigated by the yeast estrogen screen (YES) assay. The results indicate that CYL and ANA acted as agonists in the YES assay (CYL logEC50 = −8.901; ANA logEC50 = −6.789), their binding affinity to estrogen receptors is associated with their intrinsic properties, including ring structures and toxicant properties. CYL and ANA were shown to simulate endocrine disrupting chemicals (EDCs) to modulate the 17β-estradiol-induced estrogenic activity, resulting in non-monotonic dose responses. The treated CYL showed a significantly altered estrogenicity compared to the untreated CYL (T(2) = 8.168, p ≤ .05), while the estrogenicity of the treated ANA was not significantly different to the untreated ANA (T(2) = 1.295, p > .05). Intermediate products generated from CYL and ANA oxidized by Fe III -B*/H2 O2 were identified using Q-Exactive Tandem Mass Spectrometry (LC-MS/MS). Treatment with Fe III -B*/H2 O2 yielded open-ring by-products which likely resulted in CYL's reduced binding affinity to estrogen receptors. The insignificant change in the estrogenicity of treated ANA was possibly a result of its multiple ring structure products, which were likely able to bind to estrogen receptors. The comparisons for the estrogenicity of these cyanotoxins before and after Fe III -B*/H2 O2 treatment suggest that the reductions in estrogenicity achieved by oxidation were dependent on the levels of cyanotoxins removed, as well as the estrogenicity of the degradation products. This is the first study on the change in the estrogenicity of CYL and ANA upon oxidation by Fe III -B*/H2 O2, a high activity catalyst system. Graphical abstract: Image 1 Highlights: CYL and ANA act as agonist in the YES assay. CYL and ANA show concentration-dependent modulation of E2 activity. CYL and ANA have synergistic or antagonistic modulation of E2-induced estrogenicity. Fe III -B*/H2 O2 oxidation of CYL significantly decreases the estrogenicity. Fe III -B*/H2 O2 oxidation of ANA does not significantly change the estrogenicity.